Effects of Hill Land Development and Soil Erosion on Sedimentation and Water Resources in Malaysia - Ibrahim, Ab. Latif; Lateh, Habibah; Ismail, Wan Ruslan; Chan, Ngai Weng; Kung, Hsiang-te; Liu, Pin-Shuo (Universiti Sains Malaysia, 2002)
In Malaysia, water quantity and quality as well as siltation of river beds are closely connected with hill land development, soil erosion and sedimentation. Gradual depletion of developable lowland has resulted in the development of hill land, which located on the upstream of drainage basins, is extremely sensitive to human-induced environmental changes. Even small changes caused by forest clearance could lead to severe damage on natural systems such as flora, fauna, climate, hydrology and soils. Rapid development of the foothills, slopes and hill tops since the 1970s, have resulted in depletion of forest, destruction and deterioration of water catchments, changing micro-climatic elements, endangering of wild life, high rates of soil erosion, increased incidence of landslides and rockfalls, high rates of sedimentation leading to rapid siltation and reduced capacities of rivers leading to increased frequencies and magnitudes of downstream flooding, and the pollution of river water. Much of such negative impacts are also due to the disparate and uncoordinated nature in which a large number of government agencies manage drainage basins. There is a need for all drainage basins to be managed in an integrated manner in order to control hill land development and the associated impacts.